The Impact of the purchase channel on unplanned purchases - Henriques,Inês (2019)
This exploratory research aimed to observe if the purchase channel used (online versus physical store) could influence the number and the type of unplanned purchases in a supermarket purchase situation. 64 participants were asked to simulate a supermarket purchase using a shopping list and a predefined budget. Participants were divided into two conditions: online shopping and physical store shopping simulation. Findings show that consumers purchase more unplanned items (and spent more money on unplanned purchases) when they buy in physical stores, as well as items on promotion. They also tend to spend more time in the decision-making process when compared to participants shopping online. In addition, online consumers spend more money on items that were on their shopping list. Our findings are important to the literature, demonstrating that consumer reactions towards shopping differ according to the channel. Advertisers and web designers can also benefit from these findings by making better decisions regarding online advertising, specifically in the retail domain. Suggestions for future research are provided in the end.